Native english speaking teachers vs. non-native english speaking teachers - Peralta, Gabriela; Valdez, Alexandra
Globalization is connecting the world in social, economic, cultural and political aspects. This is why English has become a lingua franca (a language used among peoples whose main languages are different). Therefore, the increase of non-native teachers in the entire world is a reality nowadays. Because of this growing tendency, a stereotype has come out and it states that native teachers are better instructors than non-native teachers. The stereotype is based on the idea that native teachers own the target language. However, a debate arouse regarding the use of the term native. The pioneer of this study, Peter Medgyes, mentions that the term native should not be used since there is no ?nativity? in a language. This issue, native-non-native teachers, has provoked problems of credibility from the students? perspective, credibility from the viewpoint of professional academic organizations, and credibility in terms of administrators. Credibility is important because it has the power to disturb the students´ learning experience since if there is no trust in the teacher, people will hardly trust in his/her knowledge, which can affect the learning process. Finally, the strengths and weaknesses of both types of teachers will be analyzed to show that native as well as non-Native teachers can become successful in the teaching of the English language.